Pseudo-tumour of the trachea as a complication of tracheostomy - Żurek, Wojciech; Chwirot, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Tracheostomy is an operative procedure that creates a surgical airway in the cervical trachea. One of the indications for tracheostomy is respiratory insufficiency and prolongated artificial ventilation. Tracheostomy has a high risk of complications including risk of tracheal stenosis. The aim of this paper is to present a rare complication of tracheostomy – a pseudo-tumour of the trachea caused by subcutaneous fatty tissue herniation in the hole cut out in the tracheal cartilage. While the patient was prepared for operation, pseudo-tumour migrated by itself out of tracheal lumen. Follow up bronchoscopies showed no symptoms of pseudo – tumour relapse. Tracheostomy is an operative procedure with a high risk of complications including risk of tracheal stenosis. Correct surgical technique diminishes the risk of complications. During surgical tracheostomy one should avoid to cut a hole out of the tracheal cartilage, vertical incision of 2-nd, 3-rd and 4-th tracheal cartilages is recommended .